Idiopathic aquagenic syringeal acrokeratoderma - Nwanneka Okwundu; Stephanie Snyder-Howerte; John Young; Bill William Lear (Wolters Kluwer Medknow Publications, 2019)
Aquagenic syringeal acrokeratoderma (ASA), also known as transient reactive papulotranslucent acrokeratoderma, is an uncommon disorder that usually affects the palms. It is characterized by transient, translucent, white papules and plaques that develop upon exposure to water. Skin lesions are typically accompanied by itching and burning sensation. While many theories exist in regard to the etiology of this condition, we present a case of ASA that appears to be idiopathic in nature.